Non-enzymatic browning path analysis of ready-to-eat crayfish (Promcambarus clarkii) tails during thermal treatment and storage. (February 2023) - Jiang, Qixing; Shen, Huimin; Gao, Pei; Yu, Peipei; Yang, Fang; Xu, Yanshun; Yu, Dawei; Xia, Wenshui; Wang, Lishi
Abstract: This study was carried out to reveal the browning path of ready-to-eat (RTE) crayfish tails during thermal treatment and storage using path analysis. Maillard reactions, lipid oxidation, and phenol oxidation were evaluated in combination with free radical content and FTIR analysis, and direct path coefficients as well as determination coefficients were obtained based on these parameters, such as the absorbance at 294 nm (A294 ), 5-hydroxymethylfurfural (5-HMF), thiobarbituric acid-reactive substances (TBARS), and total phenols (TP). The result showed that the browning of seasoned RTE crayfish tails was ascribe to the synergistic effect of Maillard reaction and lipid oxidation by the order of determination coefficient. After the crayfish hepatopancreas were removed, the content of A294, 5-HMF, TBARS, and TP declined more than 30%, specifically affecting the direct pathway from lipid oxidation to Maillard reaction and alleviating the browning. However, no significant change of color was observed in the group without thirteen-spices, while TBARS and free radical content increased by at least 16.7%. The removal of hepatopancreas and the control of Maillard reaction were deemed to be a good measure for inhibiting the non-enzymatic browning of RTE crayfish tails.